A study to assess the prevalence of atypical organisms in pneumonia in children aged 1 month to 3 years by serum polymerase chain reaction in KIMS Hospital, Bangalore, India - Ramya, H. S.; Gopi, Anjana; Elango, Vivetha (International Journal of Contemporary Pediatrics, 2020)
Background: Atypical organisms are a common causative agent of pneumonia in children more than 3 years of age. Though atypical pathogens are said to cause relatively milder form of pneumonia severe manifestations can also occur. Very few studies are available on the prevalence of atypical pneumonia in children less than 3 years. Hence in this study the prevalence of atypical organisms in pneumonia was identified by using serum Polymerase chain reaction (PCR). Methods: This is a prospective observational study conducted in children between 1 month to 3 years of age with clinical diagnosis of pneumonia admitted in wards and PICU in KIMS hospital. Authors excluded Immuno compromised children. Detailed history and clinical examination was done. Investigations - complete hemogram, Chest X-ray, blood Culture and sensitivity and serum PCR was done for a sample size of 50 children. Results: Among the three atypical organisms, Legionella pneumoniae was identified in 4% (2/50) cases by serum PCR. Conclusions: In this study it was found that the prevalence of 4%. Legionella pneumonia can be fatal in 10% of cases. Hence atypical pathogens like Legionella should be kept in mind even in children less than 3 years when pneumonia is not responding to beta lactam antibiotics, in such cases macrolides to be considered.